The development paired cards using problem based learning on student competency - Ramadhani Putri Lestari; Marini Damanik; Agus Kembaren (Jurnal Pendidikan Kimia (JPKim), 2019)
This study discusses development of paired cards using problem based learning model on learning outcomes and students critical thinking skills on the oxidation reduction reactions. This study aims to find out learning outcomes and critical thinking students who taught with problem based learning model using paired cards. The populations were all students of class X MIA in High School, which consists of eight classes with a total number of students 296 students. The sample was taken by random sampling techniques is experimental class and control class. Students in experimental class were taught using problem based learning model, while control class were taught using direct instruction model. The results showed that average for the student learning outcomes 75.16 for experimental class and 70.63 for control class. The average students critical thinking skills were 40.17% for experimental class and 31.49% for control class. The student learning outcomes and critical thinking skills use problem based learning models with paired card was higher than the direct instruction model on the reduction oxidation reaction. There is a positive correlation between learning outcomes and students critical thinking skills.Keywords: Paired cards; problem based learning; oxidation reduction reaction